Principles of geochemical prospecting - Ginzbourg, I. I. (Pergamon, 1960)
The book presents the wide application of geochemical prospecting methods at all stages of the geologic service raises the need for developing some theoretical premises of such prospecting, as well as to the need for a summation of the bulky data accumulated empirically by geologic reconnaissance, geologic prospecting, and geophysical field parties